2023
DOI: 10.1139/gen-2022-0055
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome analysis of Pseudomonas furukawaii ZS1 isolated from grass carp (Ctenopharyngodon idellus) culture water

Abstract: Pseudomonas furukawaii ZS1, isolated from grass carp (Ctenopharyngodon idellus) culture water, exhibits efficient aerobic nitrate reduction without nitrite accumulation; however, the molecular pathway underlying this aerobic nitrate reduction remains unclear. In this study, we constructed a complete genome map of P. furukawaii ZS1 and performed a comparative genomic analysis with a reference strain. The results showed that P. furukawaii ZS1 genome was 6,026,050 bp in size and contained 5,427 predicted protein-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
0
0
Order By: Relevance
“…Candidatus Aquiluna, a photoheterotroph ( Kang et al, 2012 ), was reportedly positively correlated with the microbial metabolic activity of organic nitrogen ( Lukwambea et al, 2020 ). Pseudomonas furukawaii ZS1, Acidovorax facilis , Citrobacter diversus , and certain Thauera species also participate in nitrogen removal in aquaculture ponds ( Mai et al, 2021 ; Niu et al, 2022 ). Our results showed that Dechloromonas , Limnohabitans , Candidatus Aquiluna, and Pseudomonas were detected in the pond water and sediment microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Candidatus Aquiluna, a photoheterotroph ( Kang et al, 2012 ), was reportedly positively correlated with the microbial metabolic activity of organic nitrogen ( Lukwambea et al, 2020 ). Pseudomonas furukawaii ZS1, Acidovorax facilis , Citrobacter diversus , and certain Thauera species also participate in nitrogen removal in aquaculture ponds ( Mai et al, 2021 ; Niu et al, 2022 ). Our results showed that Dechloromonas , Limnohabitans , Candidatus Aquiluna, and Pseudomonas were detected in the pond water and sediment microbiota.…”
Section: Discussionmentioning
confidence: 99%